Modelling Soil Erosion Susceptibility of Johor River Basin by GIS : Modeling soil Erosion - Hussein Abed Obaid, 1979-, author; Shamsuddin Shahid, author (LAP LAMBERT Academic Publishing, 2016)
Includes bibliographical references